Omega-3 fortified yogurt and ITS influence on plasma lipid profile in an animal model - Diaz, Gabriela Esther; Foltran, Rocío Beatriz; Diaz, Silvina Laura; Feliu, María Susana; Impa Condori, Anabel Rocío; Guidi, Silvina Mabel; Ambrosi, Vanina; Nanni, Mariana Sandra; Godoy, Maria Fernanda (Sociedad Argentina de Investigación Clínica, 2023)
Poster y resumen